A study on factors influencing host resident’s perception on the impacts of tourism development on their community: A case study at Kg. Morten, Melaka / Nurul Rudzaimah Othman and Amalina Salma Mohammad Yusoff - Othman, Nurul Rudzaimah; Mohammad Yusoff, Amalina Salma (Faculty of Administrative Science and Policy Studies, 2014)
Nowadays the tourism sector has been improved and become the main focus of the government. However the government forgets to focus on the perceptions of the host residents on the impact of tourism development. There are several factors that affect the host resident’s perception such as local economy, physical environment, recreational opportunities and in-city traffic. This study is carried out to identify the factors influencing host resident’s perceptions on the impacts of tourism development in their community at Kg. Morten, Melaka. The host resident’s perception can be either positive or negative based on the benefits and costs of tourism development towards their community. The respondents are selected from resident’s in Kg. Morten, Melaka as a samples. The frequency analysis, normality analysis and Spearman’s correlation were used to analyze the data. The correlation showed that the most influential impact is in-city traffic, while the least impact is local economy. The study also showed that there is relationship between local economy, physical environment, recreational opportunities and in-city traffic towards host resident’s perceptions.